Do Rural and Suburban Principals Approach Planning Differently? A Two-State Comparison - Craig B. Howley; Aimee Howley; William Larson (Journal of Research in Rural Education, 1999)
Rural school principalsfind themselves completing school improvement plans mandated by state education agencies, largely on the model oftechnical rationality. Technical rationality, however, is just one among several approaches to planning. Because of their reputedly close connections to community and the small size of many rural schools and districts, rural principals may be more likely than other principals to adopt less formal or more incremental approaches to planning. Systems ofschooling are also organized according to historical, political, and economic conditions in the various states. Differences in state context may, therefore, influence the way rural principals approach planning. Using a research instrument grounded in theories about planning, we surveyed a stratified random sample of principals (n = 651). Results indicate significant differences by locale and by state, which are partially explained by two covarying characte ristics.